2008
DOI: 10.1097/tp.0b013e318169bebd
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Donor and Recipient Screening for Toxoplasma in the Era of Universal Trimethoprim Sulfamethoxazole Prophylaxis

Abstract: We therefore conclude that in transplant centers with low Toxoplasma seroprevalence, routine screening for Toxoplasma in solid organ donors and recipients is not necessary, particularly in the era of routine TMP/SMX prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 33 publications
1
39
0
2
Order By: Relevance
“…We also confirmed that heart transplant patients are more at risk of donor-related toxoplasmosis than other SOT patients, which has been recognized through multiple case reports and cohort studies (reviewed in reference 25). More rarely, Toxoplasma seroconversion has been described in SOT patients in the absence of clinical signs (26,27), even in patients who did not receive prophylaxis (26). Here, we observed a positive blood PCR result in two heart transplant patients who were asymptomatic.…”
Section: Discussionsupporting
confidence: 47%
“…We also confirmed that heart transplant patients are more at risk of donor-related toxoplasmosis than other SOT patients, which has been recognized through multiple case reports and cohort studies (reviewed in reference 25). More rarely, Toxoplasma seroconversion has been described in SOT patients in the absence of clinical signs (26,27), even in patients who did not receive prophylaxis (26). Here, we observed a positive blood PCR result in two heart transplant patients who were asymptomatic.…”
Section: Discussionsupporting
confidence: 47%
“…Knowledge of the serologic status of both the recipient and donor allows the start of primary chemoprophylaxis at the time of transplantation in the case of a mismatch, particularly for heart transplant patients. However, it was argued that in countries with a low Toxoplasma seroprevalence, such an occurrence is rare and that the systemic use of cotrimoxazole for the prevention of Pneumocystis pneumonia counterbalances the risk of primary Toxoplasma infection, at least in the first months following transplantation (154). If chemoprophylaxis is usually the rule for heart transplant patients in the case of a known mismatch, there is no consensus concerning the duration, which usually does not exceed 6 months.…”
Section: Screening For and Chemoprophylaxis Of Toxoplasmosis In Immunmentioning
confidence: 99%
“…However, it must be acknowledged that serologic reactivation is rarely associated with clinical reactivation but may prompt further investigation when associated with clinical signs. TMP-SMX (160 mg-800 mg) daily or three times a week is also the first-line drug regimen to prevent toxoplasmosis in SOT patients who also need to be protected against PCP (81,154,234). In the case of intolerance, pyrimethamine alone (25 mg/day) can be an alternative for T. gondii prophylaxis (234,339), and aerosolized pentamidine can be used for Pneumocystis pneumonia.…”
Section: Screening For and Chemoprophylaxis Of Toxoplasmosis In Immunmentioning
confidence: 99%
“…In France, where seroprevalence is high, serological screening is mandatory for every organ donor; screening of recipients is strongly recommended; and the risk of graft-transmitted toxoplasmosis is reduced both by prolonged chemoprophylaxis and by careful follow-up of patients in cases of mismatch. However, in countries with low Toxoplasma seroprevalence, guidelines may differ, and serological screening is not routinely recommended for all patients (18,25,34).…”
Section: Discussionmentioning
confidence: 99%
“…Heart and heart-lung transplants carry the highest risk of Toxoplasma graft transmission to a seronegative recipient (32), which can be prevented by cotrimoxazole prophylaxis (25). In high-risk mismatched heart recipients, the efficacy and safety of cotrimoxazole has been established (2,18) at the same dose regimen commonly used to prevent P. jirovecii pneumonia, but trimethoprim-sulfamethoxazole (160 and 800 mg) three times a week is also effective (2,24). In contrast, a combination of pyrimethamine and sulfadoxine (75 mg and 1,500 mg) every 2 weeks has been reported to be ineffective at preventing heart-transmitted infection (13).…”
Section: Discussionmentioning
confidence: 99%